Object-oriented Oracle - Rahayu, Johanna Wenny (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2006)
"The book covers comprehensive and fundamental aspects of the implementation of object-oriented modeling in a DBMS that was originated as a pure Relational Database, Oracle"--Provided by publisher